Analysis of the System Thinking Ability of Junior High School Students on the Main Material of the Digestive System - Aras, Julio; Jalmo, Tri; Meriza, Nadya (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This research aims to describe students' systems thinking abilities on the main material of the Digestive System. The subjects of this research were 60 students of Junior High School 8 Bandar Lampung for the 2022/2023 academic year who were selected from a population of 275 students using a cluster sampling technique. This research uses an ex post facto design. System thinking ability data was obtained through description tests which were analyzed descriptively. The results of the research show that students' systems thinking abilities are in the sufficient category for 60% of students and in the deficient category for 40% of students. The highest systems thinking ability is in the indicator of the ability to examine the character of elements with an average value of 34.25 in the sufficient category, while the lowest systems thinking ability is in the indicator of correlating interconnections with an average value of 16.11 in the deficient category. Based on the results of data calculations, it can be concluded that in general students' systems thinking abilities are in the sufficient category.Keywords: system thinking ability, digestive system